Impactul afluenţilor din dreapta asupra calităţii apelor fluviului nistru în perioada de primăvară a anului 2009 [Articol] - Duca, Gheorghe; Gladchi, Viorica; Goreaceva, Nelly; Bunduchi, Elena; Borodaev, Ruslan; Lis, Angela; Anghel, Lilia; Şurîghina, Olga; Romanciuc, Lidia (CEP USM, 2010)
Among the main factors that affect water quality of the main water resources of our country, which also ensures the economic development of the Republic, may be named the chemical flow of the tributaries waters and hydro-technical facilities, such as storage tanks.In this paper are exposed the results of researches related to the chemical composition of waters at the mouth of the tributaries of the right bank of the Dniester River - Raut, Ichel, Bic, Botna, as well as the chemical composition ofDniester waters upstream and downstream of the mouth of the mentioned above tributaries.
Keywords: ape nistrene; fluviul Nistru; calitatea apei fluviului; afluenţi